Resolvin D1 promotes efferocytosis in aging by limiting senescent cell‐induced MerTK cleavage. Issue 1 (26th November 2019) - Rymut, Nicholas; Heinz, Justin; Sadhu, Sudeshna; Hosseini, Zeinab; Riley, Colin O.; Marinello, Michael; Maloney, Jackson; MacNamara, Katherine C.; Spite, Matthew; Fredman, Gabrielle
Abstract: Inflammation‐resolution is mediated by the balance between specialized pro‐resolving mediators (SPMs) like resolvin D1 (RvD1) and pro‐inflammatory factors, like leukotriene B4 (LTB4 ). A key cellular process of inflammation‐resolution is efferocytosis. Aging is associated with defective inflammation‐resolution and the accumulation of pro‐inflammatory senescent cells (SCs). Therefore, understanding mechanism(s) that underpin this impairment is a critical gap. Here, using a model of hind limb ischemia‐reperfusion (I/R) remote lung injury, we present evidence that aging is associated with heightened inflammation, impaired SPM:LT ratio, defective efferocytosis, and a decrease in MerTK levels in injured lungs. Treatment with RvD1 mitigated I/R lung injury in aging, promoted efferocytosis, and prevented the decrease of MerTK in injured lungs from old mice. Old MerTK cleavage‐resistant mice (MerTK CR ) exhibited less neutrophils or polymorpho nuclear cells infiltration and had improved efferocytosis compared with old WT controls. Mechanistically, macrophages that were treated with conditioned media (CM) from senescent cells had increased MerTK cleavage, impaired efferocytosis, and a defective RvD1:LTB4 ratio. Macrophages from MerTK CR mice were resistant to CM‐induced efferocytosis defects and had an improved RvD1:LTB4 ratio. RvD1‐stimulated macrophages prevented CM‐induced MerTK cleavage and promoted efferocytosis. Together, these data suggest a new mechanism and a potential therapy to promote inflammation‐resolution and efferocytosis in aging.